BIOLOGY AND FISHERY OF WAM MURAENESOX TALABONOIDES (SLEEKER) - George, M K (Indian Journal of Fisheries, 2011)
Medium sized Warn, Muraenesox talabonoides (Bleeker) belonging to 110.5-130.5 cm size groups dominated the offshore catch, while size groups, smaller and larger than these mainly contributed to the inshore catch due probably io gear selection. Small sciaenids (dhoma) appear to be the favoured food ite.n of offshore warn. High incidence of empty stomachs was recorded in offshore warn. Significant deviation of sex ratio occured in wam larger than 135 cm. The length at first maturity in female is 120 cm and in male 105 cm. Fecundity varied in specimens of different length and significantly in specimens of the same length. ’Peak of spawning appears to be in May, foUowjd by a possible secondary spawning around September. Spawning ground of warn may extend from Bombay to iKutch. Wam landings formed an average 7.5 per cent of the trawler catch. Catch and catch rate were thÂ« highest in the third quarter of all the years.